Exploring mechanisms of disuse atrophy and optimal rehabilitation strategies for the restoration of muscle mass, structure & function - Inns, Thomas Benjamin (2023)
Disuse atrophy (DA) occurs during situations of unloading and is characterised by a loss of muscle mass and function. These reductions may be observed as early as 5 days into a period of unloading. While the reduction of muscle size is well studied, the reduction in muscle function is less well characterised. Furthermore, different muscles of the lower leg have been shown to express diverging profiles of muscle size loss as a result of DA. In particular, the medial gastrocnemius (MG) is relatively susceptible to DA while the tibialis anterior (TA) is resistant to even long-term bed rest of over a month. The average length of stay in hospital in the UK was last reported at 4.5 days which is enough time for DA to occur in the quadriceps. In older individuals, loss of muscle mass and function may reduce quality of life to the point of frailty and are less well suited to performing resistance exercise. Hence, alternative therapies to attenuate DA may be needed.